Heat sealability of laminated films with LLDPE and LDPE as the sealant materials in bar sealing application - Cheng, See Yuan; Ghazali, Mohd. Imran; Hassan, Azman; Ismail, Ahmad Fauzi (Wiley Periodicals, Inc., 2007)
The heat sealability of laminated films with linear low density polyethylene (LLDPE) and low density polyethylene (LDPE) as the sealant materials was investigated. A laboratory heat sealer was used to study the response of laminated films to temperature, time, and pressure. Platen temperature was confirmed as primary factor in controlling heat-seal strength. Dwell time must be sufficiently long to bring the interfacial temperature to a desired level. When the desired heat-seal strength has been achieved, further increase of dwell time did not improved heat-seal strength. Platen pressure had little effect above the level required to flatten the materials for good contact. Bar sealing process window for each sample were developed. The optimum combination of platen temperature and dwell time for each laminated film can be obtained in the respective process windows. Strength of heat-seal and its failure modes are closely related. Plateau initiation temperature closely corresponds to the final melting point of sealant materials. Relatively higher platen temperature was required to seal laminated films with lower thermal conductance. Required dwell time corresponds closely to the heat flow rate of bar sealing process. Laminated films made from extrusion lamination process provided lower level of achievable heat seal strength when compared with the laminated films made from dry-bond lamination process